Highlights of Translation Studies in China Since the Mid-Nineteenth Century - Fan, Shouyi (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractThis article attempts to highlight the thoughts of some of the prominent figures in translation studies over the past hundred years or so. With the onset of the third wave in translation activities, some patriotic scholars called for the establishment of translator training schools to meet the challenges coming from the West, while others set about introducing Western literature and philosophy into China. In the course of translating, problems cropped up, translators and scholars began to argue about what criteria they should follow, what methods they should use, and how to judge the quality of translation. As China moved into a new era, translation activities boomed and translation studies flourished, all proceeding in an orderly fashion and on a mass scale. A new wave emerged, bringing China closer to the outside world.